2008
DOI: 10.1093/abbs/40.10.883
|View full text |Cite
|
Sign up to set email alerts
|

Expression and role of factor inhibiting hypoxia-inducible factor-1 in pulmonary arteries of rat with hypoxia-induced hypertension

Abstract: Hypoxia-inducible factor-1alpha subunit (HIF-1alpha) plays a pivotal role during the development of hypoxia-induced pulmonary hypertension (HPH) by transactivating it' target genes. As an oxygen-sensitive attenuator, factor inhibiting HIF-1 (FIH) hydroxylates a conserved asparagine residue within the C-terminal transactivation domain of HIF-1alpha under normoxia and moderate hypoxia. FIH protein is downregulated in response to hypoxia, but its dynamic expression and role during the development of HPH remains u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…The top 30 signaling pathways are shown in Figure 2(c) . Previous studies have reported that the PI3K-AKT signaling pathway [ 17 ], IL-17 signaling pathway [ 18 ], TNF pathway [ 19 ], MAPK signaling pathway [ 20 ], HIF-1 signaling pathway [ 21 ], and Toll-like receptor signaling pathway [ 22 ] were related to the occurrence of PH, among which the PI3K-AKT pathway was most closely related to the treatment of PH with Shufeiya recipe ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The top 30 signaling pathways are shown in Figure 2(c) . Previous studies have reported that the PI3K-AKT signaling pathway [ 17 ], IL-17 signaling pathway [ 18 ], TNF pathway [ 19 ], MAPK signaling pathway [ 20 ], HIF-1 signaling pathway [ 21 ], and Toll-like receptor signaling pathway [ 22 ] were related to the occurrence of PH, among which the PI3K-AKT pathway was most closely related to the treatment of PH with Shufeiya recipe ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…ERK activation can promote the proliferation of pulmonary artery fibroblasts, while Shufeiya recipe can downregulate the expression levels of Ras, p-MEK1/2, p-ERK1/2, and c-fos proteins in the ERK signaling pathway, thereby inhibitting PAECs fibrosis [ 5 ]. Activation of the HIF-1 signaling pathway in PAECs can promote the proliferation of pulmonary artery medial cells, and the expression of factors such as endothelin 1 [ 21 , 29 ]. The Toll-like receptor signaling pathway is closely related to the proliferation, apoptosis, migration, and interstitial transition of PAECs [ 22 , 30 ].…”
Section: Discussionmentioning
confidence: 99%